2013
DOI: 10.1111/1475-6773.12046
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Staffing Requirements and Input Substitution: Effects on Housekeeping, Food Service, and Activities Staff

Abstract: Objective. To study the effect of minimum nurse staffing requirements on the subsequent employment of nursing home support staff. Data Sources. Nursing home data from the Online Survey Certification and Reporting (OSCAR) System merged with state nurse staffing requirements. Study Design. Facility-level housekeeping, food service, and activities staff levels are regressed on nurse staffing requirements and other controls using fixed effect panel regression. Data Extraction Method. OSCAR surveys from 1999 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Obtaining the best arrangement should be researched from the perspective of staff mix and quality of care. However, identifying the relationship between the two variables without distinction between the case mix of a resident's care demand and nursing home function has only limited explanatory power . Therefore, in the present study, the association between staff mix and quality of care considering case mix was examined in >29 beds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obtaining the best arrangement should be researched from the perspective of staff mix and quality of care. However, identifying the relationship between the two variables without distinction between the case mix of a resident's care demand and nursing home function has only limited explanatory power . Therefore, in the present study, the association between staff mix and quality of care considering case mix was examined in >29 beds.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the relationship between the two variables without distinction between the case mix of a resident's care demand and nursing home function has only limited explanatory power. 14 Therefore, in the present study, the association between staff mix and quality of care considering case mix was examined in >29 beds. We found that there was no significant difference between staff mix and quality of care through univariate analysis, but the multivariate analysis with adjusted facility characteristics showed a significant association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With our study on political control, we complement studies that analyze the effect of distinct policy initiatives, such as the effect of minimum staffing standards, certificate‐of‐need regulations, and reimbursement changes . In comparison with those studies, we analyze the full range of Republican and Democratic possibilities for policy making and how these affect the NH industry.…”
Section: Discussionmentioning
confidence: 99%